Judd–Ofelt Parametrization from the Emission Spectrum of Pr3+ Doped Materials: Theory, Application Software, and Demonstration on Pr3+ Doped YF3 and LaF3. Issue 6 (28th April 2021) - Ćirić, Aleksandar; Ristić, Zoran; Barudzija, Tanja; Srivastava, Alok; Dramićanin, Miroslav D.
Abstract: Judd–Ofelt (JO) theory explains the optical properties of trivalent lanthanides using only three intensity parameters. The JO parametrization is a complicated procedure of absorption spectra analysis, especially cumbersome for powders and non‐transparent materials. For the Pr 3+ activated materials, the procedure is additionally complicated due to strong interaction of low‐lying Pr 3+ 4f5d energy levels with the 4f levels. Here, the straightforward JO parametrization method that uses the emission spectrum and the excited state lifetime of the Pr 3+ 3 P0 level which does not require any fitting procedure are shown. In addition, the theory and software for calculations of JO parameters from Pr 3+ emission are explained. The method requirements are low‐temperature photoluminescence measurements of Pr 3+ introduced in low phonon energy hosts with a relatively high lying 4f5d energy level. The method is demonstrated on emissions of YF3 :Pr 3+ and LaF3 :Pr 3+ powders. Abstract : Judd–Ofelt, lanthanide spectroscopy centerpiece theory, allows prediction of quantities of interest from 3 parameters. Parametrization from absorption spectrum is limited to single crystals and glasses. Also, Pr 3+ has shown large discrepancies from the experimental data. This paper presents emission spectrum parametrization that is both reliable and can be applied on material in any form, tested on LaF3 :Pr 3+ and YF3 :Pr 3+ .